2014
DOI: 10.1149/06001.0709ecst
|View full text |Cite
|
Sign up to set email alerts
|

Dummy Poly Removal Impact Factors and Improvement in Hkmg Last Process

Abstract: Logic Technology and Development Center SMIC 201312For 20/16nm HK-last and MG-last process, Dummy poly is removed by Wet process. This paper studies the factors impacting the dummy poly removal process, and presents some models to explain the impacting factors. Implant process is one of main factors influencing dummy poly removal capability because the differences of implant ions and doping amount into dummy poly induce difference of poly removal rate by wet process. We also study poly surface single clean, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Both capping layer surface interface and more capping layer loss could lead to Vt shift [11]. Due to the presence of the first gate metal, the second dummy gate removal process cannot use the stronger wet process to clean byproduct/polymer [12], Hence, PET step at the end of the etching has to be adopted to remove the byproduct/polymer. The study found that by the presence of the PET step, the threshold voltage can be improved 18% (Fig 5).…”
Section: Corner Residue and Pidmentioning
confidence: 99%
“…Both capping layer surface interface and more capping layer loss could lead to Vt shift [11]. Due to the presence of the first gate metal, the second dummy gate removal process cannot use the stronger wet process to clean byproduct/polymer [12], Hence, PET step at the end of the etching has to be adopted to remove the byproduct/polymer. The study found that by the presence of the PET step, the threshold voltage can be improved 18% (Fig 5).…”
Section: Corner Residue and Pidmentioning
confidence: 99%